2012
DOI: 10.1186/1479-5868-9-53
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obese adolescents: what turns them off physical activity?

Abstract: A systematic review of qualitative studies was undertaken to understand the barriers to physical activity experienced by adolescents who were overweight or obese. From a search of electronic databases and ‘grey’ literature, published between 1950 and 2009, 15 studies met the inclusion criteria. Bronfenbrenner’s model of human development provided an ecological lens for identifying and synthesising barriers to physical activity. Two reviewers appraised study quality. Miles and Huberman’s cross-case analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 39 publications
10
141
2
5
Order By: Relevance
“…This fact is because overweight individuals are more likely to have difficulty moving around, resulting in greater economy of movement, increased energy expenditure and early fatigue in aerobic activities, reducing performance in physical tests (32). In addition, a systematic review showed that overweight adolescents tend to impose barriers to physical activity that involves individual factors such as shame of their body, interpersonal factors related to the prejudice they suffer due to excess weight, environmental factors such as lack of security in neighborhoods for physical activity, among others (33). Boys with higher CI values of this study showed lower power for health-related problems compared with other indicators (35).…”
Section: Discussionmentioning
confidence: 83%
“…This fact is because overweight individuals are more likely to have difficulty moving around, resulting in greater economy of movement, increased energy expenditure and early fatigue in aerobic activities, reducing performance in physical tests (32). In addition, a systematic review showed that overweight adolescents tend to impose barriers to physical activity that involves individual factors such as shame of their body, interpersonal factors related to the prejudice they suffer due to excess weight, environmental factors such as lack of security in neighborhoods for physical activity, among others (33). Boys with higher CI values of this study showed lower power for health-related problems compared with other indicators (35).…”
Section: Discussionmentioning
confidence: 83%
“…As predicted, obese women walked slower at selfselected speeds, had a higher oxygen consumption, and reported greater perceived exhaustion Borg scale ratings compared to normal weight women (Mattsson et al 1997). Ultimately, discomfort and fatigue resulting from PA exceeding individual physical capacity diminishes energy reserves to complete other daily non-PA related tasks and discourages future bouts of PA among obese individuals (Stankov et al 2012). …”
Section: Pain Health Concerns and Fatigue As Barriersmentioning
confidence: 76%
“…The ecological model can serve to identify physical-activityparticipation barriers across multiple systems. For example, in a recent literature review by Stankov, Olds, and Cargo (2012), 19 personal, 6 interpersonal, and 10 environmental-level participation barriers were identified for overweight and obese adolescents. Physical activity interventions incorporating the ecological model would take into consideration multiple systems that have the potential to significantly alter physical activity levels of individuals across environments.…”
Section: Discussionmentioning
confidence: 97%